HIV-associated lipodystrophy : a review from a Brazilian perspective - Alves, Marcelle Duarte (2014)
The prognosis of human immunodeficiency virus (HIV)-infected individuals has dramatically improved worldwide since the introduction of highly antiretroviral therapy. Nevertheless, along with the decrease in mortality, several body modifications not initially related to HIV infection have been reported. Disorders in lipid and glucose metabolism, accompanied by body shape abnormalities and alterations in fat distribution, began to be described. A syndrome, named “HIV-associated lipodystrophy syndrome”, was coined to classify these clinical spectrum aspects. This syndrome involves not only metabolic alterations but also fat redistribution, with lipoatrophy due to subcutaneous fat loss (predominantly in the face and lower limbs) and lipohypertrophy related to central fat gain. These changes in body shape are very important to be recognized, as they are associated with worse morbidity and mortality. Self-esteem difficulties related to body alterations might lead to treatment failures due to medication adherence problems. Moreover, these alterations have been associated with an increased risk of cardiovascular events. Therefore, it is extremely important to identify this syndrome early in order to provide an even better quality of life for this population, as the clinical approach is not easy. Treatment change, medications to treat dyslipidemia, and surgical intervention are instruments to be used to try to correct these abnormalities. The aim of this study is to review clinical presentation, diagnosis, and management of body shape and metabolic complications of HIV infection from a Brazilian perspective, a medium income country with a large number of patients on antiretroviral therapy.